testing - Muhammad Ajwad Amaluddin, 1994-; McDade, Scott; Goldbaum, Marc.; Thomas, Peter, 1924-; Lomax, Alan, 1915-2002. (Princeton, N.J. : Visual Education Corp., 1976)
Presents a people's history of the early growth of America through excerpts of authentic musical and spoken word field recordings. Each tape, covering a particular region of the country, concentrates on the social movements, occupational groups, and folk cultures of America from the early 1800s to the early 1900s. Recorded between the 1940s and the 1970s.
Northeast -- South -- Midwest -- Southwest -- Far West -- Northwest.
Visual Education Corp.: 5421-01--5421-06.
Subtitle on container: An oral history of the American people.
Produced, directed, and written by Scott McDade; co-written by Marc Goldbaum; listener's guide introduction by Alan Lomax.
In container (29 cm.).
Peter Thomas.
Keywords: Oral history; Folklore -- United States; United States -- Social life and customs -- 19th century; United States -- Social life and customs -- 1865-1918.